The maturation of auditory responses in infants and young children: a cross-sectional study from 6 to 59 months - Edgar, J. Christopher; Murray, Rebecca; Kuschner, Emily S.; Pratt, Kevin; Paulson, Douglas N.; Dell, John; Golembski, Rachel; Lam, Peter; Bloy, Luke; Gaetz, William; Roberts, Timothy P. L. (Frontiers in Neuroanatomy, 2015)
Background: An understanding of the maturation of auditory cortex responses in typically developing infants and toddlers is needed to later identify auditory processing abnormalities in infants at risk for neurodevelopmental disorders. The availability of infant and young child magnetoencephalography (MEG) systems may now provide near optimal assessment of left and right hemisphere auditory neuromagnetic responses in young populations. To assess the performance of a novel whole-head infant MEG system, a cross-sectional study examined the maturation of left and right auditory cortex responses in children 6- to 50-months of age. Methods: Blocks of 1000Hz (1st and 3rd blocks) and 500Hz tones (2nd block) were presented while MEG data were recorded using an infant/young child biomagnetometer (Artemis 123). Data were obtained from 29 children (11 males; 6 months to 59 months). Latency measures were obtained for the first positive-to-negative evoked response waveform complex in each hemisphere. Latency and age associations as well as frequency and hemisphere latency differences were examined. For the 1000 Hz tone, measures of reliability were computed. Results: For the first response - a response with a ‘P2m’ topography - latencies decreased as a function of age. For the second response - a response with a ‘N2m’ topography - no N2m latency and age relationships were observed. A main effect of tone frequency showed earlier P2m responses for 1st 1000 Hz (150 ms) and 2nd 1000 Hz (148 ms) versus 500 Hz tones (162 ms). A significant main effect of hemisphere showed earlier N2m responses for 2nd 1000 Hz (226 ms) versus 1st 1000 Hz (241 ms) versus 500 Hz tones (265 ms). P2m and N2m interclass correlation coefficient latency findings were as follows: left P2m (0.72, p < 0.001), right P2m (0.84, p < 0.001), left N2m (0.77, p < 0.001), and right N2m (0.77, p < 0.01). Conclusions: Findings of strong age and latency associations, sensitivity to tone frequency, and good test-retest reliability support the viability of longitudinal infant MEG studies that include younger as well as older participants as well as studies examining auditory processing abnormalities in infants at risk for neurodevelopmental disorders.